2008
DOI: 10.11646/zootaxa.1884.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Phytoseiid mites (Acari: Phytoseiidae) from Argentina, with description of a new species

Abstract: This paper reports the mites of the family Phytoseiidae known from Argentina. It is based mostly on a survey conducted in the northern region of that country as well as on published information. Twenty-two species were found in that survey, ten of which are new records from that country, including a new species here described as Neoseiulus argentinus Guanilo & Moraes n. sp.. Measurements of all species collected and a taxonomic key to separate the species known to date from Argentina are provided. All toge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(13 citation statements)
references
References 0 publications
0
12
0
1
Order By: Relevance
“…They stated the "movable cheliceral digit 25 long, with 1 tooth; fixed cheliceral digit 26 long, with 3 teeth". A study of a voucher specimen of Guanilo et al (2008b) from San Miguel de Tucumán revealed that the movable cheliceral digit has 3 teeth and fixed cheliceral digit has 5 teeth, in agreement with those of N. californicus sensu Athias-Henriot (1977). Tixier et al (2008) followed the concept of N. californicus sensu Athias-Henriot (1977) and removed N. marinus from synonymy with "N. californicus" sensu Athias-Henriot (1977); they reexamined of a paratype of N. marinus and confirmed the absence of teeth on the movable digit.…”
Section: The Identity Of Neoseiulus Californicusmentioning
confidence: 77%
See 1 more Smart Citation
“…They stated the "movable cheliceral digit 25 long, with 1 tooth; fixed cheliceral digit 26 long, with 3 teeth". A study of a voucher specimen of Guanilo et al (2008b) from San Miguel de Tucumán revealed that the movable cheliceral digit has 3 teeth and fixed cheliceral digit has 5 teeth, in agreement with those of N. californicus sensu Athias-Henriot (1977). Tixier et al (2008) followed the concept of N. californicus sensu Athias-Henriot (1977) and removed N. marinus from synonymy with "N. californicus" sensu Athias-Henriot (1977); they reexamined of a paratype of N. marinus and confirmed the absence of teeth on the movable digit.…”
Section: The Identity Of Neoseiulus Californicusmentioning
confidence: 77%
“…These agree with N. californicus sensu Athias-Henriot (1977) as redescribed in this paper. Guanilo et al (2008b) redescribed N. californicus from Argentina. They stated the "movable cheliceral digit 25 long, with 1 tooth; fixed cheliceral digit 26 long, with 3 teeth".…”
Section: The Identity Of Neoseiulus Californicusmentioning
confidence: 99%
“…Colonies were kept on new and completely expanded trifoliate strawberry leaves, with petiole placed in water-filled tubes (height 7 cm, diameter 2 cm) to keep the leaves turgid, inside a box (500 ml) covered with paper film to prevent individuals from escaping. Due to the morphological similarity of N. californicus with other species, phytoseiids were identified according to Schuster and Pritchard (1963) and Guanilo et al (2008). Individuals of N. californicus were supplied, every 2 days, with eggs, nymphs and adults of T. urticae as food, using a fine brush of sable hair.…”
Section: Laboratory Assaysmentioning
confidence: 99%
“…Distribution. South America: Argentina (Guanilo et al 2008a), Brazil (Ferla & Moraes 1998), Colombia (Moraes & Mesa 1988), Ecuador (Moraes et al 1991), Peru (Guanilo et al 2008b).…”
Section: Proprioseiopsis Neotropicusmentioning
confidence: 99%